Compressive strength of concrete blended with Bagasse ash and lime sludge - Opiso, Einstine M. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2014)
Thousands of tons of bagasse ash and lime sludge which have potential cementitious properties are generated from the two sugar milling companies in Bukidnon and are currently dumped in their respective open disposal sites. This study aimed to examine the potential utilization of bagasse ash and lime sludge as the partial replacement (up to 30%) of Ordinary Portland Cement (OPC) in concrete. The results showed that the compressive strength of concrete, using bagasse ash and lime sludge as the partial replacement of OPC, failed to meet the minimum requirement of 21 MPa which is set bt the National structural Code of the Philippines (NSCP) (2010), except for samples using 10% of lime sludge as the partial replacement to cement (T4). Moreover, the blending ratio of 40% bagasse ash to 60% lime sludge as a partial replacement of OPC showed promising results. However, further studies should be conducted to determine the effect of different blending ratio of bagasse ash and lime sludge and water cement ratio in order to study their distinctive effect during pozzolanic reaction.